Second form at malory towers - Blyton, Enid (Mammoth London, 2000)
Back to malory Towers and in the second form now, Darrell and her friends know that they should be a little more grown-up. But sometimes sheer mischief gets the better of them and thjey think they can get the better of the mistresses. Are they about to go one trick too far?